Therapeutic Roles of Tendon Stem/Progenitor Cells in Tendinopathy - Xin Zhang; Yu-cheng Lin; Yun-feng Rui; Hong-liang Xu; Hui Chen; Chen Wang; Gao-jun Teng (Stem Cells International)
Tendinopathy is a tendon disorder characterized by activity-related pain, local edema, focal tenderness to palpation, and decreased strength in the affected area. Tendinopathy is prevalent in both athletes and the general population, highlighting the need to elucidate the pathogenesis of this disorder. Current treatments of tendinopathy are both conservative and symptomatic. The discovery of tendon stem/progenitor cells (TSPCs) and erroneous differentiation of TSPCs have provided new insights into the pathogenesis of tendinopathy. In this review, we firstly present the histopathological characteristics of tendinopathy and explore the cellular and molecular cues in the pathogenesis of tendinopathy. Current evidence of the depletion of the stem cell pool and altered TSPCs fate in the pathogenesis of tendinopathy has been presented. The potential regulatory factors for either tenogenic or nontenogenic differentiation of TSPCs are also summarized. The regulation of endogenous TSPCs or supplementation with exogenous TSPCs as therapeutic targets for the treatment of tendinopathy is proposed. Therefore, inhibiting the erroneous differentiation of TSPCs and regulating the differentiation of TSPCs into tendon cells might be important areas of future research and could provide new clinical treatments for tendinopathy. The current evidence suggests that TSPCs are promising therapeutic targets for the management of tendinopathy.